Kinesthetic Learning Style and PAI Learning Outcomes of Elementary School Students - Ramdhan, Tri Wahyudi; Masuwd, Mowafg Abrahem (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to determine the influence of the kinesthetic learning style on the learning outcomes of Islamic Religious Education (PAI) among Year 4 students at MIN Bangkalan. This research employs a quantitative approach with a purposive sampling technique involving 36 participants. The research data were obtained through a kinesthetic learning style questionnaire, observations, and a learning outcomes test on the topic of Friday prayer. Data analysis techniques included the Kolmogorov-Smirnov normality test, Pearson correlation analysis to examine the relationship between kinesthetic learning style and PAI learning outcomes, and simple regression analysis to assess the impact of kinesthetic learning style on students' academic performance. The findings indicate a significant influence of kinesthetic learning style on PAI learning outcomes, with a significance value (2-tailed) of 0.000. Students with a kinesthetic learning style exhibit characteristics such as enhanced recall through movement and hands-on practice, as well as a preference for physical activity. These findings suggest that the application of kinesthetic learning strategies can serve as an effective approach to improving PAI learning outcomes among primary school students, particularly in subjects requiring practical comprehension.